Evaluation of self‐collected rectal swabs for the detection of bacteria responsible for sexually transmitted infections in a cohort of HIV‐1‐infected patients. Issue 6 (June 2017) - Edouard, Sophie; Tamalet, Catherine; Tissot‐Dupont, Hervé; Colson, Philippe; Ménard, Amélie; Ravaux, Isabelle; Dhiver, Catherine; Tomei, Christelle; Stein, Andreas; Raoult, Didier
Abstract : Purpose. : The standard approach to screening sexually transmitted infections (STIs) has often been restricted to urogenital specimens. Most current guidelines, however, also recommend testing extra‐genital sites, including rectal locations, because asymptomatic rectal carriage of pathogens has often been reported. The aim of our study was to evaluate self‐collected rectal swabs to screen bacterial STIs in HIV‐infected patients in Marseille, France. Methodology. : Between January 2014 and December 2015, 118 HIV‐infected patients (93 males and 25 females) agreed to self‐sample anal swabs for detection of bacterial STI. Detection of Neisseria gonorrhoeae, Chlamydia trachomatis, Treponema pallidum, Mycoplasma genitalium and Haemophilus ducreyi was performed using in‐house qPCR assay. Results/Key findings. : Bacterial STIs were found in 8% (9/118) of the patients. C. trachomatis was the most commonly detected bacterium (4.2%) followed by N. gonorrhoeae (2.5%), M. genitalium (1.7%) and T. pallidum (0.8%). All the positive patients were males. The rectal carriage of pathogenic bacteria was fortuitously discovered for seven men (78%) who did not present rectal signs of STIs and was suspected for two men who presented proctitis (22%). Conclusion. : In conclusion, testing extra‐genital sites is crucial for the diagnosis of STIs in men and women presenting or not concomitant urogenital infections in order to detect asymptomatic carriage with the aim of controlling and preventing transmission to their sexual partners.